(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
Nowadays publications on the frequency of prolonged jaundice in full-term are becoming published more frequently, which dictates a more detailed study of the possible long-term effects of damage to the infant’s CNS, in addition to the previous studies of bilirubin encephalopathy, kernicterus and Cerebral Palsy. Analysis of modern literature and probable clinical variants of neurodevelopment disorders of infants who had prolonged jaundice.